Effect of different polishing system on bis-acryl material surface roughness and gloss: experimental study - Khuzairi, Hafidz Al; Kodasi, Cintya; Andryas, Ika; Wahyuni, Siti (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACT Introduction: Bis-acryl composite resins are commonly used for temporary crowns but are difficult to polish due to their soft resin and hard filler particles. Well-polished surface on temporary crowns offers benefits like better gingival-health, improved mastication, and better aesthetics. Multi-step aluminum oxide discs and one-step diamond discs are effective for polishing bis-acryl materials. This study aimed to analyze the surface roughness and gloss of bis-acryl provisional crowns before and after polishing with two different polishing systems. Methods: Total of 72 samples (10x2 mm and 16x2 mm) were divided into two groups (I and II) for roughness and gloss analysis. Each group was further subdivided into four sub-groups (IA,IIA,IB, and IIB). Groups IA and IIA were polished using the aluminum oxide multi-step system, while groups IB and IIB were polished using the diamond one-step system. All samples were pre-standardized with abrasive paper #1000 before polishing. Surface roughness and gloss were measured using profilometer and glossmeter before and after polishing. The data were analyzed using paired t-test (p<0.05). Results: After polishing, the surface roughness for the aluminum oxide group was 0.18±0.02, with gloss value of 46.55±1.31. The diamond disc resulted in surface roughness of 0.15±0.02 and gloss value of 51.08±1.76. Statistically significant differences were found in surface roughness and gloss between groups IA and IB (p=0.0001), delta gloss between groups IIA and IIB (p=0.0001). Conclusions: Both polishing systems produced acceptable surface roughness (0.20 μm) and gloss (40-60 GU). However, the diamond one-step system produced a smoother and glossier surface with greater efficiency. KEY WORDS: Bis-acryl, surface roughness, gloss, aluminum oxide, diamond Pengaruh perbedaan sistem pemolesan terhadap kekasaran dan kilap permukaan pada material bis-acryl: studi eksperimental ABSTRAKPendahuluan: Resin komposit bis-acryl sering digunakan untuk mahkota sementara, namun sulit dipoles karena kombinasi resin lunak dan partikel filler keras. Permukaan mahkota yang dipoles memberikan keuntungan dalam perawatan gigi, seperti kesehatan gusi, pengunyahan, dan estetika. Disk aluminium oksida dan disk diamond dianggap efektif untuk pemolesan bahan bis-acryl. Penelitian ini bertujuan untuk mengevaluasi kekasaran dan kilap permukaan bahan mahkota sementara bis-acryl sebelum dan sesudah pemolesan dengan dua sistem pemolesan yang berbeda. Metode: Sebanyak 72 sampel bis-acryl berbentuk disk (10x2 mm dan 16x2 mm) dibagi menjadi dua kelompok (kelompok I dan II) untuk evaluasi kekasaran dan kilap permukaan. Setiap kelompok dibagi lagi menjadi empat sub-kelompok (IA, IIA, IB, IIB). Kelompok IA dan IIA dipoles dengan disk aluminium oksida sistem multi-langkah, sedangkan kelompok IB dan IIB dipoles dengan disk diamond sistem satu langkah. Sebelum pemolesan, semua sampel distandarisasi menggunakan kertas abrasif #1000 dengan rotary grinder. Profilometer dan glossmeter digunakan untuk mengukur kekasaran dan gloss permukaan. Kemudian data dianalisis menggunakan uji t berpasangan (P<0.05).Hasil: Setelah pemolesan, kekasaran permukaan dengan disk aluminium oksida adalah 0,18±0,02 dengan gloss 46,55±1,31. Dengan disk diamond, kekasaran permukaan menjadi 0,15±0,02 dengan gloss 51,08±1,76. Uji T menunjukkan perbedaan signifikan pada kekasaran dan gloss antara kelompok IA dan IB (p=0,0001), serta perbedaan signifikan pada gloss antara kelompok IIA dan IIB (p=0,0001). Simpulan: Kedua sistem pemolesan menghasilkan kekasaran permukaan dan gloss yang dapat diterima, namun disk diamond menghasilkan permukaan yang lebih halus dan mengkilap dengan efisiensi lebih tinggi. KATA KUNCI: Bis-acryl, kekasaran permukaan, kilap, aluminum oksida, diamond